Motion Compensation Technique Based On Fractional Fourier Transform - Tan Gewei; Pan Guangwu; Lin Eei (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Fractional Fourier transform(FrFT) is a kind of generalized Fourier transform, which processes signals in the unified time-frequency domain and the linear frequency modulation signal can be well focused after FrFT. Motion error is an important factor affecting the SAR resolution, pointing to the problem that the effect of error elimination is not obvious in processing non-stationary motion error using the traditional FFT based motion compensation combined SAR imaging algorithm, FrFT based two-step motion compensation combined wavenumber domain algorithm and sub-aperture wide beam motion compensation algorithm are put forward in this paper, which are expected to eliminate the influence of motion error more effectively, so as to obtain high quality SAR images. The simulation results and the imaging results of real SAR data show that the proposed algorithms indeed eliminate the influence of motion error effectively. (the real SAR data provided by Institute of Electronics, Chinese Academy of Sciences). DOI : http://dx.doi.org/10.11591/telkomnika.v12i6.5478